Exploring Female Relatives of Patients with Hemophilia’ Awareness, Attitudes, and Understanding Towards Genetic Testing - Zhao H; Geng WJ; Wu RH; Li ZZ (Journal of Multidisciplinary Healthcare, 2024)
Hua Zhao,1 Wen-Jing Geng,2 Rui-Hong Wu,3 Zhen-Zhen Li3 1College of Nursing, Shanxi University of Chinese Medicine, Jinzhong, Shanxi, People’s Republic of China; 2Nursing Department, Third Hospital of Shanxi Medical University, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, Tongji Shanxi Hospital, Taiyuan, Shanxi, People’s Republic of China; 3Department of Hematology, the Second Hospital of Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of ChinaCorrespondence: Hua Zhao, College of Nursing, Shanxi University of Chinese Medicine, Jinzhong, Shanxi, 030619, People’s Republic of China, Tel +86 13903465019, Email zhshun7788@126.comPurpose: A better understanding of the factors that influence engagement is needed to provide a reference for conducting genetic testing in female relatives of patients with hemophilia (PWH). We therefore determined the perceptions and understanding of genetic testing among female relatives of PWH in China.Methods: We carried out a qualitative study using in-depth, semi-structured interviews with 11 female relatives of PWH in Shanxi Province, China. The resulting data were analyzed using thematic analyses.Results: This study extracted four topics: uncertainty about carrier genetic status; limited understanding of genetic testing; coexistence of positive and negative coping; and multi-aspect demands.Conclusion: Healthcare professionals should provide personalized and multidimensional health education and comprehensive decision-making support to female relatives of PWH, to enhance their motivation and willingness to undergo genetic testing. It is also important to actively improve relevant policies, strengthen the genetic testing service system, and promote the popularization of genetic testing in female relatives of PWH.Keywords: hemophilia, female, genetic testing, attitudes, qualitative study